Penerapan Metode Total Physical Response (TPR) untuk Meningkatkan Keterampilan Kosakata Bahasa Inggris bagi Siswa Tunagrahita - Nur Endah Nugraheni; Lukas Danu Kristian (Universitas Gadjah Mada, 2018)
This study aims to understand the use of Total Physical Response or TPR method to improve English vocabulary skill of students with mental retardation. Students with mental retardation are students who have an IQ score less than 70 on a psychological test of intelligence; therefore, they have difficulty in learning including learning English. TPR is a fun method to teach students with mental retardation. The subject of this study was eight students with mental retardation of the 11th grade in SLB N Kota Magelang. To investigate the TPR method, the researchers did direct teaching to the students. Pre-test was given before TPR method was employed then post-test was done afterwards. By comparing the pre-test and post-test score, the result shows that the students’ average score increases after the TPR method was implemented. The highest score in pre-test is 90 and the lowest score is 60. Meanwhile, the highest score in post-test is 100 and the lowest score is 70. The average score in pre-test is 71,25 and the average score in post-test is 87,50. It can be concluded that Total Physical Response method was successfully implemented in increasing the students’ English vocabulary skill.